Estabilidade de cor de laminados cerâmicos após a cimentação com cimentos resinosos e resinas compostas aquecidas: acompanhamento de 12 meses - Gugelmin, Brenda Procopiak (2018)
The objective of this study was to evaluate the color stability of thin ceramic laminate veneers luted with resin cements and heated composite resins (60o C) for 12 months, as well as detremine the degree of conversion of the different luting agents. Two resin cements (AllCem – dual-cured (CRD) and AllCem Veneer – light-cured resin cement (CRF)] and three composite resins [Z100 (RCPF – fine particles), Herculite Classic (RCMH – micro-hybrid) e Durafill (RCMP – microparticles)] were used for cementing 0.8 mm-thick lithium silicate glass-ceramic laminates (Suprinity, shade B2 - HT) on bovine enamel. Eighty specimens were randomly divided into 8 groups according to the luting material (n = 10). After cementation and throughout the whole experiment, the specimens were stored in distilled water at 37°C. The CIELab color parameters were determined with a spectrophotometer (Easyshade Advance) at 24 hours after luting (baseline), 7, 30, 90, 180 days and 12 months. The degree of conversion (n = 3) was determined by micro-Raman spectroscopy (Senterra). The color stability data were analyzed by one-way ANOVA with repeated measures and Tukey’s test. For the degree of conversion, data were analyzed by one-way ANOVA and Tukey's test. All anyalyzes were perforemd with a significance level of 5%. For color change, the results indicated significant differences for luting material (p = 0.0006) and time (p < 0.0001). For the luting material, the mean ΔE values representing the lowest and highest variation were, respectively: CRD (1.48 ± 0.75), RCMP-AQ (2.35 ± 1.34) and RCMP (2, 50 ± 1.26). The mean ΔE values varied significantly over the 1-year period, being greater than 3.3 only for RCMP (3.6 ± 1.0) and RCMP-AQ (3.6 ± 1.6) groups. Regarding the degree of conversion, there were no statistically significant differences (p = 0.1268) among the tested luting materials. The degree of conversion ranged from 64.0% (RCPF-AQ) to 85.1% (CRD). A moderate to strong negative correlation was observed between the mean ΔE in the evaluated period and the degree of conversion, with Pearson's correlation coefficient of -0.68. It can be concluded that the different luting agents used for the cementation of thin ceramic laminate veneers influenced the final color of the restorations. The heating of the composite resins did not alter their degree of conversion.